Muslim’s awareness and willingness to patronize Islamic banking in Kazakhstan - Abduh, Muhamad; Omarov, Daniyar (International Association of Islamic Banks, 2013)
Islamic banking was an abstract concept until the first half of the twentieth century. In Kazakhstan, it has been only three years since the first Islamic bank made its debut. Islamic banks have to compete with their rival, conventional banks, which have far longer history than Islamic banks. This competition urges Islamic banks to know the awareness and willingness of Muslim in Kazakhstan upon them. The purpose of this research is to examine the level of awareness and willingness of Muslims to patronize Islamic banking in Kazakhstan. Thus, a total number of 300 respondents from different cities of Kazakhstan were collected and descriptive analysis methods were adopted. The results show that more than half of the respondents are aware of Islamic banking in Kazakhstan, but they are not aware of most of the products and services offered by Islamic banks. Interestingly, despite the moderate level of Muslim Kazakhs understanding towards Islamic banking concepts, the willingness level of using Islamic banking products and services is high.